09.01 Armoring anti-HER2 CAR-T cells with C-C-motive receptor 8 (CCR8) and a dominant negative TGF-b receptor (DNR) to enable efficacy in solid tumor models. (21st September 2022) - Strzalkowski, TJ; Cadilha, BL; Dalloul, I; Manske, K; Endres, S; Kobold, S
Abstract : Background: Chimeric antigen receptor (CAR) T cells have shown great efficacy in treating hematological malignancies. Nonetheless, in solid tumors CAR T cells have yet to demonstrate significant clinical efficacy. In solid tumors, CAR T cells are frequently prevented access to tumor tissue and face profound suppression at the tumor site. To overcome this issue, our group could previously demonstrate that arming CAR T cells with C-C-motive-receptor 8 for improved tumor-directed migration along the C-C-chemokine ligand 1 - CCR8 axis and a dominant-negative receptor against TGF-β for resistance to suppression enable activity in pancreatic cancer models. The value of this approach for other entities was however unclear. We now investigated the potential of this combination for treatment of HER2-positive cancer models in conjunction with a HER2-targeted CAR. Materials and Methods: Primary murine and human T cells were isolated and activated. T cells were retrovirally transduced. Phenotype, activation, exhaustion and proliferation were monitored in vitro . Cytokine production was assessed with ELISA. In vivo, survival and tumor growth of mice that were subcutaneously injected with tumor cells and treated with CAR T cells carrying either CCR8, DNR or both receptors were measured. To look at chemokine expression in tumor material, mRNA was isolated from tumor material and RT-qPCR was performed. Results: We found that expression of CCR8 can redirect CAR T cells to the tumor and a DNR can prevent immunosuppression of CAR T cells in the tumor microenvironment. The improved functionality of CAR-CCR8-DNR T cells compared to CAR T cells against the HER2 antigen could be demonstrated in vitro and in vivo in human HER2+ tumor models. Conclusions: Equipping CAR T cells with CCR8 and DNR emerges as a strategy not only limited to certain antigens, but as a potential universal approach to render cellular therapies more effective. The modularity of this concept promises further preclinical and perhaps clinical development to improve personalized immunotherapy. Disclosure Information: T.J. Strzalkowski: None. B.L. Cadilha: A. Employment (full or part-time); Significant; University Hospital, LMU Munich. I. Dalloul: A. Employment (full or part-time); Significant; University Hospital, LMU Munich. K. Manske: A. Employment (full or part-time); Significant; University Hospital, LMU Munich. S. Endres: A. Employment (full or part-time); Significant; University Hospital, LMU Munich. B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; TCR2 Inc, Bio-M, Munich, Germany. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Significant; Else Kröner-Fresenius Stiftung, Paul-Martini-Stiftung. E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Carina Biotech Ltd, Mawson Lakes, Australia. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; TCR2, Cambridge, MA, USA. F. Consultant/Advisory Board; Significant; Gilde Healthcare, Utrecht, Netherlands. S. Kobold: A. Employment (full or part-time); Significant; University Hospital, LMU Munich. B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; TCR2 Inc, Arcus. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Modest; Bristol-Myers Squibb, GlaxoSmithKline. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Significant; Novartis. E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Carina Biotech Ltd, Mawson Lakes, Australia. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; TCR2, Cambridge, MA, USA. F. Consultant/Advisory Board; Modest; Tabby therapeutic ltd. F. Consultant/Advisory Board; Significant; TCR2 Inc, Novartis.